Proceedings of the 21st ACM International Conference on Information and Knowledge Management 2012
DOI: 10.1145/2396761.2398476
|View full text |Cite
|
Sign up to set email alerts
|

Empirical validation of the buckley-osthus model for the web host graph

Abstract: We consider the Buckley-Osthus implementation of preferential attachment and its ability to model the web host graph in two aspects. One is the degree distribution that we observe to follow the power law, as often being the case for real-world graphs. Another one is the two-dimensional edge distribution, the number of edges between vertices of given degrees. We fit a single "initial attractiveness" parameter a of the model, first with respect to the degree distribution of the web host graph, and then, absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In [26] it was shown that the behavior of d nn (d) in the Buckley-Osthus model (with carefully chosen parameter which corresponds to the degree distribution with infinite variance) is very similar to the one observed for the web host graph.…”
Section: A < 1/2mentioning
confidence: 59%
“…In [26] it was shown that the behavior of d nn (d) in the Buckley-Osthus model (with carefully chosen parameter which corresponds to the degree distribution with infinite variance) is very similar to the one observed for the web host graph.…”
Section: A < 1/2mentioning
confidence: 59%
“…In particular, in this article, the authors use the undirected relations of bidirectional virtual "friendship", subsequently the users mentioned "Buddhism" Later in the article the authors will make an empirical evaluation of a number of important topological characteristics of the graph of Buddhists in "Vkontakte" (Zhukovskii et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The exponent was determined by Albert and Barabási (2002) to be 2.1 ± 0.1 and by Maxim Zhukovskiy et al (2012) to be 2.276 ± 0.001. That is, the log of the number of ASs with N in-links on the Internet is a linear function of the log of ASs with a gradient of about − 2.2.…”
Section: The Ba Model and Attraction To Popularitymentioning
confidence: 99%